The Effect of Teamwork and Work Discipline on Employee Performance with Organizational Commitment as A Mediation Variable (Empirical Study at Bumi Akpelni Polytechnic Semarang) - Victor Wiku Widyo Bharoto (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this research is to analyze the effect of teamwork and work discipline on employee performance with organizational commitment as a mediating variable. The population in this study were 161 employees of the Bumi Akpelni Polytechnic Semarang. Sampling in this study used a purposive judgment sampling method, 101 permanent employees were taken. Samples were taken using the census method. Data processing method using SPSS. The results of hypothesis testing show that teamwork has a positive and significant effect on organizational commitment, that the better the teamwork, the higher the organizational commitment. Work discipline has a positive and significant effect on organizational commitment. Organizational commitment has a positive and significant effect on employee performance, so employee performance is getting better. Teamwork has a positive and significant effect on employee performance, the better the teamwork, the better the employee performance. Work discipline has a positive and significant effect on employee performance, the better the work discipline applied, the better employee performance.